Bioproduction of p-Hydroxystyrene from Glucose by the Solvent-Tolerant Bacterium Pseudomonas putida S12 in a Two-Phase Water-Decanol Fermentation - Verhoef, Suzanne (American Society for Microbiology (ASM), 2009)
Two solvent-tolerant Pseudomonas putida S12 strains, originally designed for phenol and p-coumarate production, were engineered for efficient production of p-hydroxystyrene from glucose. This was established by introduction of the genes pal and pdc encoding l-phenylalanine/l-tyrosine ammonia lyase and p-coumaric acid decarboxylase, respectively. These enzymes allow the conversion of the central metabolite l-tyrosine into p-hydroxystyrene, via p-coumarate. Degradation of the p-coumarate intermediate was prevented by inactivating the fcs gene encoding feruloyl-coenzyme A synthetase. The best-performing strain was selected and cultivated in the fed-batch mode, resulting in the formation of 4.5 mM p-hydroxystyrene at a yield of 6.7% (C-mol of p-hydroxystyrene per C-mol of glucose) and a maximum volumetric productivity of 0.4 mM h(−1). At this concentration, growth and production were completely halted due to the toxicity of p-hydroxystyrene. Product toxicity was overcome by the application of a second phase of 1-decanol to extract p-hydroxystyrene during fed-batch cultivation. This resulted in a twofold increase of the maximum volumetric productivity (0.75 mM h(−1)) and a final total p-hydroxystyrene concentration of 21 mM, which is a fourfold improvement compared to the single-phase fed-batch cultivation. The final concentration of p-hydroxystyrene in the water phase was 1.2 mM, while a concentration of 147 mM (17.6 g liter(−1)) was obtained in the 1-decanol phase. Thus, a P. putida S12 strain producing the low-value compound phenol was successfully altered for the production of the toxic value-added compound p-hydroxystyrene.